The use of gastrocnemius muscle flap in trauma - Mohd Yusof, Nazri; Mohd Kasim, Kamil; Khalid, Kamarul Ariffin; Che Ahmad, Aminudin; Mohd Amin, Azril (2007)
Gastrocnemius flap is a common flap done in orthopaedic practice because of its simplicity and reliability. However, complications have happened when technical details and careful planning were not observed. We reported case series on gastrocnemius flap done in our institution over a four years period. There were 11 cases of gastrocnemius flap which was done to cover soft tissue defect following infection after plate fixation, infected open fracture and open grade IIIB tibial fracture. Ten cases healed uneventfully while one cases had early wound breakdown which was salvaged by repeated wound debridement and a fasciocutaneous flap. The clinical application, practical consideration, its advantages and limitations are discussed.